2019
DOI: 10.1177/0091415019848211
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Designation of a Substitute Decision-Maker in Older Asian Americans: The Role of Cultural Factors

Abstract: The present study examined the prevalence of and factors associated with the designation of a substitute decision-maker (SDM) in a sample of older Asian Americans. Particular emphasis was placed on cultural factors (ethnicity, time in the United States, English proficiency, acculturation, and cultural belief) that might influence on one’s attitudes toward death and dying or end-of-life decision-making. Data were drawn from the 499 participants aged 60 years and older using the 2015 Asian American Quality of Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Another explanation may be that the observed differences reflect the preferences and influence of family caregivers. While family is consistently endorsed as a key player in EOL decisionmaking among Asian Americans, [44][45][46][47][48][49] intergenerational differences in acculturation level complicate our understanding of familial roles at the EOL. 50 Future research into the mechanism by which Asian families make EOL decisions will enable the delivery of family-centered, goal-concordant, and culturally tailored EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that the observed differences reflect the preferences and influence of family caregivers. While family is consistently endorsed as a key player in EOL decisionmaking among Asian Americans, [44][45][46][47][48][49] intergenerational differences in acculturation level complicate our understanding of familial roles at the EOL. 50 Future research into the mechanism by which Asian families make EOL decisions will enable the delivery of family-centered, goal-concordant, and culturally tailored EOL care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies adopted the SDH framework to examine the associations between social determinants and end-of-life outcomes, such as the use of hospice or palliative care, completion of advance directives or use of aggressive treatments (Brown et al, 2018;Koroukian et al, 2017;Rhee & Jang, 2020). Health literacy is one of the major SDH, and end-of-life specific health literacy-awareness or knowledge of hospice or palliative care-has been found to predict individuals'…”
Section: Socialdeterminantsofhealthmentioning
confidence: 99%
“…For example, in the US, autonomy is an empowering attribute while in Korea, it is burdensome (Blackhall et al, 1995) because Koreans prefer collective, family-based decision making over individualistic, patient-centered decision making (Newman et al, 2006). Acculturation to an individualistic culture may increase the need for autonomy among members of collectivistic cultures (Hamamura, 2012;Rhee & Jang, 2019); a study of seniors of multiple ethnicities living in New York indicated that they were uncomfortable delegating end-of-life decisions to family (Morrison et al, 1998). Collectivist cultures, on the other hand, impede individual decision making by removing the patient from euthanasia decisions (Blackhall et al, 1995), sometimes not even informing them about impending death (Schwartz, 2004).…”
Section: Influence Of Culture In Shaping Attitude Towards Euthanasiamentioning
confidence: 99%
“…This, in turn, affects candor; full disclosure of illness to patients is more likely in the US and European cultures vis-à-vis others (Ersek et al., 1998). The lack of candor is compounded by cultural beliefs against speaking about death (Rhee & Jang, 2019) held by Chinese and Mexicans, among others (Carrese & Rhoades, 1995).…”
Section: Impetus and Relevance Of The Topicmentioning
confidence: 99%